“WAJAH LUMER” ABJEKSI DAN KRITIK MORAL DALAM MANGA DISSOLVING CLASSROOM KARYA JUNJI ITO - Ramdhan, Asep (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2025)
This study analyzes the story “Melting Face” in Junji Ito's horror manga “Dissolving Classroom” through visual analysis and the concept of abjection. The story depicts bodies and faces melting as a result of excessive apologies and praise, which is not only visually frightening but also contains symbolic meaning and social criticism. Through visual reading of key panels, it is revealed that the deformation of faces in the narrative depicts the collapse of individual identity under the pressure of repressive social norms and cultural politeness in contemporary Japanese society. This study shows that the horror in Dissolving Classroom functions as a metaphor for oppressive social experiences and manipulation in interpersonal relationships. The symbolism of melting faces represents the conflict between self-expression and hypocritical moral expectations. This finding affirms that Junji Ito's work is not merely a product of popular horror but also a critical reflection on cultural dynamics and social anxieties in modern society.